استخدام نظم المعلومات الالكترونية وأثره على أمن وسلامة المعلومات المحاسبية: The use of electronic information systems and their impact on the security and safety of accounting information (Journal of Academic Research, 2019)
The study aims to explore the effect of using electronic accounting information systems on the information security and safety, and the most important risks that has impacted on accounting information and the procedures to protect the information security and safety. To achieve objectives of the study the researcher developed a questionnaire and distributed it to staffs in two companies which are Al Zawiya Oil Refining Company and Mellitah Oil & Gas Companyand Brega Company than the date collected and analyzed using SPSS softwere.The study had reached the following results:1-  There was not a different impact of using electronic accounting information systems on the information security and safety between Az Zawiya Oil RefiningCompany and Mellitah Oil & Gas Company and Brega Company.2-  There were enough procedures to protect the information security and safety in the companies.